The Korean Buddhist empire a transnational history (1910-1945) - Kim, Hwansoo Ilmee 1970- (Harvard East Asian monographs, 2018)
"Highlights the centrality of transnational relationships in the transformation of colonial Korean Buddhism in the early twentieth century. While Japanese Buddhism exerted the most influence, Korean Buddhism (and Japanese Buddhism itself) was deeply influenced by developments in China, Taiwan, and elsewhere, as well as by Christianity"--Provided by publisher.